PTU-218 Pilot randomised cross-over study comparing the efficacy of transnasal Endosheath® to standard endoscopy to detect Barrett's oesophagus. (28th May 2012) - Shariff, K M; Verghese, S; O'Donovan, M; Abdullahi, Z; Blazeby, J; Fitzgerald, R C
Abstract : Introduction: A less expensive and safer alternative to standard sedated endoscopy (SE) needs to be considered as a screening method to detect Barrett's oesophagus (BE) in the population, with the aim of reducing the mortality associated with oesophageal adenocarcinoma. The Endosheath® transnasal oesophagoscope (TNE) can potentially offer a new alternative to conventional standard endoscopy in diagnosing Barrett's oesophagus. The Endosheath® technology uses a sterile, disposable sheath which covers the ultra thin flexible oesophagoscope and isolates it from the patient. The oesophagoscope is placed in a new sheath prior to each procedure which obviates the need for machine washing and permits a quick turnaround. Aim: A pilot study to evaluate the efficacy of TNE in diagnosing BE compared with SE and to assess patient acceptability of TNE. Methods: Patients referred for surveillance endoscopy for BE or a clinically indicated routine endoscopy were recruited to both TNE and SE in a randomised cross-over design. The interval between the procedures was at least 6 weeks. TNE findings of endoscopic BE, and presence of intestinal metaplasia (IM) on the biopsy samples were compared against SE, which was used as gold standard. A 10-point visual analogue scale (0 represented the worst experience and 10 the best experience) to assess the post-endoscopy experience and a single question addressing preference for endoscopy type were used to measure patient acceptability of the procedures. Results: 15 patients completed the study, 10 males and 5 females with a mean age of 62.85 years (range 50–76 years). Nine of which were BE surveillance patients and six were referred for a clinically indicated routine endoscopy. Eight patients were randomised to the SE as the first procedure. All the 11 patients with an endoscopic diagnosis of BE on SE were accurately identified with the TNE (sensitivity 100%; specificity 100%). Biopsies were taken in all the 11 Barrett's segments except in one <1 cm segment with TNE due to technical difficulty. IM was detected in 9 out of the 11 patients with BE on SE compared to 7 out of the 11 patients with BE on TNE (sensitivity 77.8%; specificity 100%). Patients reported significantly better experiences of endoscopy with TNE with scores of 6.9 (±0.81 SEM) compared with 3.7 (±0.37 SEM) for SE (p=0.001). Eight patients (53%) reported a preference for TNE compared with 1 (7%) for SE. Conclusion: Endosheath® transnasal oesophagoscope is accurate in diagnosing endoscopic BE and can detect IM. It is better tolerated and preferred by patients, making it a useful screening tool for BE with potential for use in primary care. Competing interests: None declared.